Applied zooarchaeology : five case studies - Wolverton, Steve; Nagaoka, Lisa Ann; Rick, Torben C. (Principles of archaeology (Eliot Werner Publications, Inc.), 2016)
During the last two decades, zooarchaeologists have increasingly focused aspects of their work on conservation biology. Zooarchaeological data represents an empirical record of past human-animal interactions, which provides conservation with a deep temporal perspective. There are many challenges that face the archaeologist as conservation biologist, however, that have little to do with deep time, faunal remains, and zooarchaeological method and theory. This book uses a series of case studies with which each of the authors has relevant personal experience to explore the types of interdisciplinary challenges that zooarchaeologists face when crossing into the world of environmental management and animal conservation. Never has there been a greater need for multi-vocal perspectives in conservation biology. This book shows zooarchaeologists how to use zooarchaeological perspectives to help meet those needs, while crossing traditional academic disciplinary boundaries.